Comparative Evaluation of Age Estimation by Pulp Tooth Ratio with and without Grid: A Cross-sectional Study - Reethu Ravichandiran; Ramasamy Sarvathikari; Venkatesh Jayaraman; K Ramya; Vijayalakshmi Lakshmanan; Sakthivel Sambasivam (Journal of Clinical and Diagnostic Research)
Introduction: Adult age estimation may be essential in post-mortem identification, and its significance is increasing in the field of forensics for both living and deceased persons. Using forensic odontology, one can accurately identify a person’s race, age, and sex, as well as differentiate one group from another. Aim: To estimate and compare dental age using the mandibular first molar by the Pulp Tooth Ratio (PTR), with and without a grid. Materials and Methods: A cross-sectional study was conducted among subjects in Chidambaram, Tamil Nadu, India from January 2021 to December 2021. The study sample comprised 150 Orthopantamograph (OPGs). The tracing measurements were performed on the Joint Photographic Experts Group (JPEG) images using Adobe Acrobat 7.0 Professional software. A novel method, incorporating a grid in all the Orthopantomograms (OPG), was used to improve the accuracy of image tracing. The measurements were performed with and without the grid; the images were consistently zoomed to 160%, and the grid used was 0.1 cm × 0.1 cm. The tracing values were used to estimate age by the PTR. Statistical analysis was conducted using IBM Statistical Package for Social Sciences (SPSS) Statistics Version 20.0. An Unpaired T-test, Pearson’s Correlation, and linear regression were performed. Results: In the age-wise comparison between the two techniques, the mean dental age of the mandibular first molar using the PTR with and without the grid did not show statistical significance (p-value=0.951). The present study found no difference between the methods with and without the grid, showing highly correlated values using the PTR with and without the grid of -0.671 and -0.744, respectively. These r values are statistically significant (p-value <0.05), reflecting that the estimated age by both methods correlated with chronological age. Conclusion: There was no statistical difference between the dental age estimated using the mandibular first molar by the PTR with and without the grid.